Do Chronic Diseases and Availability of Medications Predict Post-traumatic Stress Disorder (PTSD) among Syrian Refugees in Jordan? - Al-Smadi, Ahmed Mohammad; Halaseh, Hanan Jameil; Gammoh, Omar Salem; Ashour, Ala Fawzi; Gharaibeh, Besher; Khoury, Laurice Sami (Pakistan Journal of Nutrition, 2016)
Objectives: The primary objective of this study was to examine if previous Chronic Diseases (CDs), newly diagnosed CDs in Jordan and medication shortages can predict PTSD in a cohort of Syrian refugees residing in Jordan. Materials and Methods: A cross-sectional study design was used. Approximately, 765 Syrian refugees were recruited from six different cities in Jordan. Data were collected using a demographical data sheet and a PTSD scale. Logistic regression was used to examine the impact of factors that showed significant association with the PTSD category. Results: Descriptive analysis of PTSD categories showed that the majority (81%) had lower PTSD scores. Moreover, PTSD was comorbid with chronic diseases in more than half of participants. Logistic regression analysis indicated that job status and availability of medications were predictors of PTSD. Conclusion: Job status and availability of medications were shown to be important factors that may influence PTSD among refugees. Further studies of additional factors and screening for mental health diseases for residing and coming refugees are recommended.